Integrating mental health literacy into Chinese college student mental health education in the post-COVID-19 era - Gao, Tao; Gao, Bo; Wang, Linzhao; Qing, Zaihua (Frontiers in Public Health, 2024)
This study investigates the influence of COVID-19 on the mental health of Chinese college students and evaluates the current status of mental health literacy (MHL) education. With mental health issues among students becoming increasingly prominent due to the pandemic and rapid social changes, enhancing MHL is critical. The research highlights the necessity of integrating mental health education with MHL to foster resilience and effective coping strategies. It proposes a model combining online and offline education to maximize accessibility and engagement. By examining both domestic and international perspectives, the study underscores the importance of comprehensive mental health education reform in the post-pandemic era. This integrated approach aims to improve students' mental well-being, reduce stigma, and encourage help-seeking behaviors, ultimately contributing to a healthier and more supportive campus environment.